Experience, authority and tradition in the making and playing of classical guitars: a hermeneutic interpretation - Rudi Bower (Acta Academica, 2012)
The making of musical instruments is an ancient human pursuit. However, to a large extent, this art-form has evaded academic and philosophical enquiry. Most of the theoretical work on the subject is illustrative and includes technical or practical approaches. This article links the building of classical guitars, or luthiery, in a South African and global manifestation, with the writings of hermeneutic thinker Hans-Georg Gadamer. It will investigate notions of experience, authority and tradition relating to luthiery. Interviews with selected South African luthiers will be used to substantiate the relevance of Gadamer’s thoughts to luthiery.